Peningkatan Kemampuan Berpikir Kritis Melalui Cards Of The Formula Pada Perkuliahan Mekanika - Baiq Aryani Novianti; Sapiruddin Sapiruddin (Kappa Journal, 2019)
This research aimed at improving critical thinking ability of the fourth  semester students in mechanics course of physics education at  Universitas Hamzanwadi. Method applied was  problem based learning through lesson study activity which covered open class four cycle. Media used was cut of papers contained  formula or mathematics equation which were called Cards of the formula, the cards were given in every open class activity. The data of critical thinking ability taken from critical thinking test administered by the end o, pices of f lecturing activity. Qualitative data taken from obseravtion result during the lecturing. From the activity, it was found that studentsâ€™ critical ability in every element namely giving argument ability , formulating problem,  doing induction, and by doing deduction, average scores above 3 was got which were categorized into high and medium.